The Use of Formal Language in English Debate Forums on YouTube - Siregar, Deasy Yunita; Maryam, Annajmi Mastari; Aiya, Naliza; Septiani, Nasywa Dwi; Fataya, Azzurra; Mahrani, Eka; Salsabila, Alfia (MUDABBIR Journal Research and Education Studies, 2025)
This study examines the use of formal language in English debate forums on YouTube by analyzing authentic utterances produced by debaters and moderators in formal debate settings. Using a qualitative descriptive approach, this research analyzes three debate videos, including Youth Leadership Debate competitions and a Harvard student debate held at the John F. Kennedy Jr. Forum. The data consist of selected utterances taken directly from debate transcripts that reflect formal language use in openings, argumentation, disagreement, and closing statements. Brown and Levinson’s Politeness Theory is employed to explain how speakers manage disagreement while maintaining professionalism and social harmony. The findings show that formal language in debate forums is realized through institutional greetings, structured argument framing, mitigated criticism, and evaluative closing statements. Expressions such as formal audience address, guided argument markers, and indirect disagreement demonstrate that formality in debate goes beyond basic politeness and is shaped by academic and institutional norms. This study highlights the importance of formal spoken English in debate contexts and suggests that debate videos on YouTube provide valuable data for analyzing academic oral discourse.